A circulating exosomal microRNA panel as a novel biomarker for monitoring post‐transplant renal graft function. Issue 20 (11th September 2020) - Chen, Yimeng; Han, Xu; Sun, Yangyang; He, Xiaozhou; Xue, Dong
Abstract: Accurate and effective biomarkers for continuous monitoring of graft function are needed after kidney transplantation. The aim of this study was to establish a circulating exosomal miRNA panel as non‐invasive biomarker for kidney transplant recipients. Plasma exosomes of 58 kidney transplant recipients and 27 healthy controls were extracted by gel exclusion chromatography and characterized by transmission electron microscopy, nanoparticle tracking analysis and Western blotting. Post‐transplant renal graft function was evaluated by estimated glomerular filtration rate (eGFR). Quantitative real‐time polymerase chain reaction was used to determine the expression of exosomal microRNAs (miRNAs). Exosomal miR‐21, miR‐210 and miR‐4639 showed negative correlations with eGFR in the training set and were selected for further analysis. In the validation set, miR‐21, miR‐210 and miR‐4639 showed the capability to discriminate between subjects with chronic allograft dysfunction (eGFR < 60 mL/min/1.73 m 2 ) and those with normal graft function (eGFR > 90 mL/min/1.73 m 2 ). Three‐miRNA panel exhibited higher accuracy compared with individual miRNAs or double indicators. One‐year follow‐up revealed a stable recovery of allograft function in subjects with low calculated score from three‐miRNA panel (below the optimal cut‐off value). In conclusion, a unique circulating exosomal miRNA panel was identified as an effective biomarker for monitoring post‐transplant renal graft function in this study.